Exploring Challenges and Solutions to Prevent and Overcome Bullying Behavior Among Vocational School Students - Wardah, Ani; Auliah, Nurul; Aminah, Aminah; Andriyani, Riya; Pebrianti, Novi (Kuras Institute, 2024)
Bullying continues to be a significant problem in educational settings, adversely affecting the psychological, physical, and social well-being of kids. This study investigates the difficulties and solutions for preventing and mitigating bullying among Vocational High School (SMK) students in Banjarmasin, Indonesia. Data were gathered via written and semi-structured interviews with four guidance and counseling educators from public and private vocational institutions Using a qualitative research methodology and case study design. The thematic analysis identified three primary challenges: the perception of bullying as a